Nature-Based Solutions for Improving Resilience in the Caribbean : 360° Resilience Background Paper - Valero, Sara (World Bank, Washington, DC, 2021)
Sustainable management of environment and natural resources is essential for the long-term and sustainable growth of key economic sectors, such as fisheries, forestry or tourism, across the Caribbean. In addition to being important generators of GDP and beneficial to the human well-being overall, natural resources also provide a range of ecosystem services that play a critical role in the Caribbean countries’ efforts to reduce disaster risks and adapt to mounting climate change risks. The region is facing a number of challenges in this area, including the climate change impacts, limited access to financing, and narrow fiscal space, among others. Such challenges are being exacerbated by the unprecedented health, economic and social impacts of COVID-19 pandemic. However, with great challenges come great opportunities, including to grow and shift the development pathway into a green recovery, based on the richness of the natural resources and biodiversity that this region possesses.